Delta's key to the TOEFL @ test (Delta Publishing Company, 2001)
Delta’s Key to the TOEFL Test is a comprehensive TOEFL preparation course. It is the first totally new TOEFL prep course to unlock the mysteries of the computerized TOEFL and the traditional paper–based test. The course design is based on sound instructional theory. Fifty–four units of study each zero in on a specific skill in listening, language structure, reading, or writing. All units include a focus exercise, many sample test items, discussion of TOEFL “tricks,” several practice exercises, extension activities, and a skill assessment. The new “computer–unique” test items are clearly described with tips.